Estudo de prevenção e controle da COVID-19: percepção e práticas no cotidiano das orientações médico-científicas por diabéticos atendidos em um território de abrangência da Atenção Primária à Saúde em um município do estado do Maranhão, Brasil - LOPES, Érika Sales (2022)
The COVID-19 pandemic declared in March 2020 by the World Health Organization (WHO) caused researchers from around the world to mobilize to understand the disease and its impact on populations. It was found that people with comorbidities were at increased risk of mortality from COVID 19, especially people with diabetes, making it necessary to implement strategies and recommendations for this specific group. The objective of this work is to analyze how diabetics treated in a territory covered by Primary Health Care in a municipality in the State of Maranhão, Brazil, perceive and translate prevention and control measures into everyday practices at the individual, family and collective levels. of COVD-19. This cross-sectional study had a quantitative-qualitative approach, having been carried out in the territory covered by Primary Care in the municipality of São José de Ribamar – MA, being a multicenter project. The questionnaire was applied to 52 families, a sample defined by convenience. Data collection in the first stage was through an online questionnaire on the Google Forms platform. In the second stage, 20% of the families participating in the previous stage and who were diagnosed with diabetes responded to the scheduled and audio-recorded interview, following the saturation criterion. For the majority of interviewees, the media was the main source for obtaining information about prevention, the most reliable and with which they felt best informed. Regarding the information provided by health professionals, the majority felt very well informed or well informed. We can highlight the role of community health agents in this process. The use of alcohol gel, use of masks and social distancing measures were the main prevention measures considered. During the interviews, participants expressed their distrust regarding the dubious information and fake news disseminated, and vaccination was cited as an effective prevention measure.